Development of a screening tool for reading readiness and early literacy skills in elementary students: mapping reading challenges and support practices - Deden Mulyadi; Adi Adinugroho; Patricia Lestari Taslim (Literal: Disability Studies Journal, 2025)
Early reading readiness plays a critical role in children’s academic development, yet many students in Indonesia continue to face challenges in acquiring foundational literacy skills. This study aims to map early reading readiness and reading difficulties among children in preschool to Grade 2 in the Thousand Islands, representing the initial stage of developing a contextually appropriate early literacy screening tool. A total of 309 parents and 48 teachers participated using purposive sampling. Data were collected through parent and teacher questionnaires, whose reliability values improved after item refinement (parents: 0.496 → 0.605; teachers: 0.395 → 0.619). Quantitative results revealed several key findings: 76.7% of households lacked dedicated reading spaces, 51.4% of children were not yet reading independently, and 68.7% of Grade 1 students entered school unable to read. Teachers reported high proportions of decoding (72.9%) and comprehension difficulties (58.3%), with comprehension problems being the most frequently identified (total 196 cases). These findings align with the Simple View of Reading and Scarborough’s Reading Rope, indicating that weaknesses in phonemic awareness, decoding, and language comprehension form the core of early reading challenges in this region. The study’s implications highlight the urgent need for an early literacy screening tool that integrates environmental factors, instructional variability, and children’s foundational skills. Such a tool can support early identification and targeted intervention, particularly in geographically unique regions like the Thousand Islands. However, the study is limited by its regional specificity, use of self-report data, and the exploratory nature of the instruments. Future research should expand to multiple regions, incorporate direct child assessments, and involve external expert validation to strengthen the tool development process.